Disparities in Land Economic Value in Public Acquisition: Contextual Islamic Legal Reconstruction of Regulatory Gaps and the Threat of Land Mafia - Agus Triono; Andriyan Syaputra; FX Sumarja; Ima Frafika Sari; Makmur Harun (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
This study examines disparities in land economic value in public land acquisition in Indonesia, focusing on distortions generated by land mafia practices. Employing a normative juridical approach with statutory, conceptual, and comparative analyses, this research integrates land value theory, justice theory (John Rawls), legal philosophy (Gustav Radbruch), and maqāṣid al-sharī‘ah as developed by Jasser Auda. The findings reveal that land value inequality is not merely a market-driven phenomenon but is structurally produced by regulatory loopholes, weak law enforcement, and institutional vulnerability, which collectively enable land mafia networks to manipulate land valuation, ownership documentation, and compensation mechanisms. These conditions result in unfair redistribution of economic benefits, marginalization of lawful landholders, and delays in public development projects. This study argues that existing positive law frameworks, particularly Law No. 2 of 2012 on Land Acquisition for Public Interest, emphasize formal legality but insufficiently address substantive justice and property protection. To address this gap, the research proposes a contextual reconstruction of Islamic law grounded in ḥifẓ al-māl (protection of property), ‘adl (justice), and maṣlaḥah (public interest). This reconstruction operationalizes maqāṣid al-sharī‘ah into concrete regulatory strategies, including transparent valuation standards, participatory compensation models, integrated digital land administration, institutional accountability, and community legal empowerment. The novelty of this study lies in transforming maqāṣid al-sharī‘ah from a normative ethical framework into an operational legal instrument for land governance reform. By integrating Islamic legal principles with positive law, this research offers a conceptual model for addressing land value inequality and strengthening protection against land mafia practices, contributing to the development of a more just, transparent, and socially sustainable land acquisition system.